DICER1 syndrome and embryonal rhabdomyosarcoma of the cervix: a case report and literature review - Stambouli, Alexandre; Cartault, Audrey; Petit, Isabelle Oliver; Evrard, Solene; Mery, Eliane; Savagner, Frederique; Trudel, Stephanie (Frontiers in Pediatrics, 2023)
Background Embryonal rhabdomyosarcomas (ERMS) of the uterine cervix and corpus are rare pediatric tumors usually associated with a late age of onset and frequent somatic DICER1 mutation. It may also develop in the context of a familial predisposition such as DICER1 syndrome requiring specific medical care for children and young adults at risk for a broad range of tumors. Case presentation This is a case of a prepubescent 9-year-old girl who was presented to our department for metrorrhagias due to a vaginal cervical mass, initially classified as a müllerian endocervical polyp on negative myogenin immunostaining. The patient subsequently manifested growth retardation (-2DS) and learning disabilities leading to genetic explorations and the identification of a germline pathogenic DICER1 variant. The family history revealed thyroid diseases in the father, aunt and paternal grandmother before the age of 20. Conclusion Rare tumors such as cervical ERMS associated with a family history of thyroid disease during infancy could be related to DICER1 syndrome. Identifying at-risk relatives is challenging but necessary to detect early DICER1 spectrum tumors in young patients.